Media application feature video creative thinking Ability to improve the students in learning ipsa - Rubianti, Teni Dwi (Universitas Pendidikan Indonesia, 2017)
This research background based on the problems that occur in class VII-A SMP Negeri 5 Bandung associated with creative thinking abilities of learners in the social studies learning. These issues are the findings of the observations made at some time in January 2017. Indicators of the problems encountered is the creative thinking ability of students is still relatively low, these problems among which, the students are less able to find information about the problems that exist in the subject matter. This is evidenced by the number of students who answered questions teacher from textbooks alone, without any attempt to explore from various other sources of information. Learners are less able to associate the subject matter contained in daily life - today. This indicates that learners are not sensitive to the surrounding environment, causing learners do not know the state of the environment. In answering questions from the teacher the students do not think holistically (comprehensive), learners are not able to think and look at various aspects and approaches, but stu is so broad assessment. Reviewing the problems to be studied with regard to the learning process, the researchers chose a Class Action Research (PTK) Kemiss research design and Taggart 3 cycles. The selected alternative solutions is through the use of media feature video is expected tocreative thinking abilities of learners to be increased. The increase in creative thinking abilities of learners in the social studies learning can be seen from several indicators of achievements of creative thinking ability has increased. All aspects of this have evolved from the first cycle to the third cycle of sufficient quality, to be good. In conclusion, the media use feature the video can improve creative thinking ability of students in social studies learning.